LANGUAGE FUNCTIONS IN @onlyjiungs TWITTER ACCOUNT - Vicha Chairunissa; Chusni Hadiati; Tri Wahyu Setiawan Prasetyoningsih (Universitas Islam Negeri Sunan Gunung Djati, 2023)
This study aimed to identify the language function in tweets from @onlyjiungs. The @onlyjiungs Twitter account's tweets served as the study's source of data. Purposive sampling and the descriptive qualitative approach were utilized in this study to get the answers to its research questions. The findings indicated that among the 31 data, the referential function (14 utterances, or 45,2%) is most frequently used, followed by the expressive function (11 utterances, or 35,5%), the phatic function (2 utterances, or 6,4%), the metalingual function (0%), the conative function (2 utterances, or 6,4%), and the poetic function (2 utterances, or 6,4%). The tweets from @onlyjiungs met every requirement in Hymes' (1974) theory of context SPEAKING, showing that context SPEAKING on a tweet from @onlyjiungs answers every requirement of the theory. The tweets were taken from September 2021 through October 2021. The goals of @onlyjiungs' tweets were intended to be represented and expressed in the final sections of the Twitter post outcomes. The following social act update about Jiung's life was provided by @onlyjiungs. She underlined a particular statement she made in the tweets. Because, they were intended for teens their age, @onlyjiungs's tweets are also frequently written in a casual tone. The typical Twitter tweet mostly focused on describing the purpose of and the message included inside it. The kind of utterances from those tweets generally had a stronger referential function since those Twitter postings' primary purpose was to notify @onlyjiungs' followers who are the readers. Keywords: language functions, context, pragmatics, twitter